The Role of Renewable Energy in Reducing Carbon Emissions: Evidence From 10 Countries Successful in The Environmental Performance Index (Third Sector Social Economic Review, 2025)
Today, increasing environmental concerns and climate change have further increased the importance of renewable energy sources. Considering the environmental impacts of the use of fossil fuels, the transition to renewable energy is seen as a critical step towards a sustainable future. In this context, understanding the effects of renewable energy consumption (REN) on CO2 emissions is of great importance for shaping environmental policies. The aim of this study is to examine the relationship between renewable energy consumption and CO2 emissions in ten countries (Estonia, Luxembourg, Germany, Finland, United Kingdom, Sweden, Norway, Austria, Switzerland and Denmark) that are successful in the environmental performance index for the period 1990-2021. In the study, Dynamic Common Correlated Effects (DCCE) and Panel Vector Error Correction Model (VECM) Causality test are used. The DCCE analysis findings reveal that the increase in renewable energy consumption has a significant effect on reducing CO2 emissions both in the overall panel and in individual countries. Moreover, according to the panel VECM causality test, there is a long-run causality from renewable energy consumption to CO2 emissions. In line with these findings, ten countries that are successful in the environmental performance index are successful in reducing CO2 emissions by using renewable energy resources effectively and thus contribute to sustainable development goals.
Keywords: Renewable Energy Consumption; Dynamic Common Correlation Effects; Panel VECM Causality; Environmental Performance Index; CO2 Emissions